Pengembangan Media Permainan Edukatif Jenga Pintar (Jetar) Tema Ekosistem Untuk Meningatkan Minat Belajar Peserta Didik Sekolah Dasar - Khasanah, Sholekhah Nur; Hendracipta, Nana; Andriana, Encep (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The aim of this research and development is to understand the process of developing the educational game media Jenga Smart with the ecosystem theme, its feasibility, student responses, and the students' learning interest after using this media. This media contains content related to thematic learning, specifically Theme 5 "Exploring Ecosystems" and Sub-theme 1 "Ecosystem Components," Lesson 2. The research method used is the Research and Development (R&D) method. The development model employed in this study follows the ADDIE development model, consisting of five stages: Analysis, Design, Develop, Implement, and Evaluation. Data collection techniques include interviews, observations, questionnaires, and documentation. The subjects of this study are 20 fifth-grade students from SDIT Tarbiyah Rabbaniyyah. The research findings indicate that the average validation score from the expert team is 89.09%, falling under the "Very Eligible" category. Additionally, students' responses to this media have an average score of 88.83%, which falls under the "Very Good" category. Similarly, the students' learning interest has increased, with an average score of 66% before using the media, categorized as "Moderate", and 92.25% after using the media, categorized as "High". In conclusion, the Jenga Smart educational game media is suitable for use and can enhance students' learning interest.